Engagement marketing for social good: Application to the All of Us Research Program - Lewis, Megan A.; Uhrig, Jennifer D.; Adams, Elizabeth T.; Brown, Jill A.; Sanders, Amy; , the RTI International All of Us Innovator Team (Frontiers in Genetics, 2022)
Engagement marketing, when applied to increasing the social good, involves making a deliberate effort to engage communities with an organization’s brand that might not have otherwise happened organically. Organizations that typically focus on increasing the social good include non-profits, community organizations, public health departments, and federal, state, and local agencies. Engagement marketing builds relationships, gives a voice to, and fosters collaboration with community members to transform their insights into impactful experiences that motivate and empower them to act to increase the social good. These actions may include making an informed decision, changing a health or prosocial behavior, or joining an effort that promotes or increases social good. In this paper, we translate the commercial engagement marketing approach, typically used, and studied widely to increase profits, to one that uses engagement marketing to increase prosocial outcomes. We propose a new definition of engagement marketing applied to the social good, a multi-level conceptual framework that integrates individual, social, community and macro-level processes and outcomes, and illustrates how we are applying this translated model to co-create digital engagement experiences using a human centered design approach for the All of Us Research Program. This model can also guide research and practice related to DNA-based population screening.